Eficacia de la anestesia raquídea con bupivacaína 0.5% isobárica comparada con anestesia epidural en cesáreas por preeclampsia severa - Ortíz Chávez, José Roger (2014)
Regional anesthesia has advantages over general anesthesia in pregnant. In our environment epidural and spinal anesthesia is used, however there is controversy by choosing one of these methods in relation to the risk of hypotension and the effects on the mother and fetus using spinal anesthesia; therefore propose the research study, comparative, analytical and observational. METHODS: We included 84 pregnant women with severe preeclampsia between 18 and 45 years, ASA II and III, who received epidural anesthesia (Group A) or spinal anesthesia (Group B) with 42 patients in each group. We recorded age, ASA, operative time, latency period, SBP, DBP, MAP, heart rate, hypotension, bradycardia, nausea, vomiting, chills, high and total blockade. RESULTS: Age, ASA, operative time were similar in both groups. We found significant differences in the latency period, mean DBP and MAP during the first 10 minutes and the mean SBP during the first 20 minutes (p <0.05). Were not found significant differences when comparing the mean differences in heart rate; well as to compare hypotension, bradycardia, nausea, vomiting, chills, high block and total block. CONCLUSIONS: Spinal anesthesia is more effective than epidural anesthesia in relation to the latency period. Both methods are effective anesthetics in relation to hipoptension, bradycardia and heart rate; although there is a greater decrease in blood pressure during the first 10 minutes using spinal anesthesia. No significant differences in complications